Wartime and Post-War Confiscations of East Asian Objects Held in the Collections of the Celje Regional Museum - Davor Mlinarič (Asian Studies)
The article attempts to clarify, on the basis of laws adopted during and after the Second World War, how East Asian items became part of the museum collections held today by the Celje Regional Museum (Pokrajinski muzej Celje, PMC). The first part of the article focuses on confiscations of cultural and historical objects carried out by the Nazis in Lower Styria (Untersteiermark) between 1941 and 1945. The second part of the article covers the period immediately after the end of the Second World War. This was the period that saw the start of the formation of so-called national property, in other words the passage of ownership from private to state hands. As will be shown, a series of laws regulating the new authorities’ attitude towards property were passed in a relatively brief period. In the summer of 1945, the task of collecting cultural and historical objects was taken over by collection centres established for this purpose. One such collection centre was located in Celje. With the help of archival sources, we have attempted to shed light on its operations.